A Formation Control Method for AUV Group Under Communication Delay - Chen, Yuepeng; Guo, Xuan; Luo, Guangyu; Liu, Guangwu (Frontiers in Bioengineering and Biotechnology, 2022)
This paper presents a consistency control algorithm for the autonomous underwater vehicle (AUV) group combined with the leader-follower approach under communication delay. Firstly, the 6-degrees of freedom (DoF) model of AUV is represented, and the graph theory is used to describe the communication topology of the AUV group. Especially, a hybrid communication topology is introduced to adapt to large formation control. Secondly, the distributed control law is constructed by combining consensus theory with the leader-following method. The consistency control algorithms for homogeneous and heterogeneous AUV groups based on the leader-follower approach under communication delay are proposed. Stability criteria are established to guarantee the consensus based on Gershgorin disk theorem and Nyquist law, respectively. Finally, numerous simulation experiments are carried out to show the effectiveness and superiority of the proposed algorithms.